Cultural diversity and health, another approach to equity: effects of the implementation of the transcultural program for medical assistance at the hospital italiano de buenos aires health insurance program - Santagata, Mónica (Revista del Hospital Italiano de Buenos Aires, 2005)
Background.In the year 2000, we designed and implemented the "Transcultural Program for Medical Assistance" (TPMA), an intervention to induce a change in the organizational behavior with the purpose of increasing equality in health (access, acceptance, availability and comfort), originally applied to Chinese and Korean patients, who were members of a private health insurance system. Objectives. To study the effect of the implementation of TPMA. Design. Retrospective, quasi-experimental, pre-posttest study. Population. Chinese and Korean members of the health insurance program at the Hospital Italiano de Buenos Aires. Conclusions. Since the implementation of TPMA, there was an increase in the number of office consults (utilization), and in the new membership rates. At the end of the evaluation period, 70% of the population identified had utilized a “bilingual, cultural facilitator”